Identification on SNP polymorphisms associated with meat productivity in the local Kazakh horse breed - Kabylbekova, D.; Ussenbekov, Y.; Assanbayev, T.; Bekmanov, B.; Kassymbekova, Sh. (Fundamental and Experimental Biology, 2023)
The aim of our study was to genotype local horses of the Kazakh breed, including the Zhabe u types from the Pavlodar and Zhetysu regions, as well as the Adai type from the Mangystau region, using PCR-RFLP methods for the LCORL and PRKAG3 gene loci. A total of 41 horses were included in the study. The results showed that the frequency of the homozygous genotype TT at the LCORL locus was 81.25% in Zhabe Pavlodar horses, with a heterozygous genotype TC of 18.75%. In Kazakh horses of the Adai type from Mangystau and Zhabe type from Zhetysu, no genetic polymorphism was detected, and all individuals had a homozygous genotype – TT. For the PRKAG3 locus, genetic polymorphism was only found in Adai type horses, with one mare out of 17 tested horses having a heterozygous genotype – CT (5.89%). Horses of the Zhabe type in Pavlodar and Zhetysu regions had a single homozygous CC genotype. The level of homozygosity for the LCORL gene locus in the three studied groups was: 81.25, 100.0 100.0. For the PRKAG3 gene is 100.0, 94.11, 100.0. The level of heterozygosity for the LCORL gene locus in horses of Pavlodar region was 18.75%, for the PRKAG3 gene locus in horses of Mangistau region 5.89%. Thus, LCORL and PRKAG3 gene polymorphisms play a significant role in determining the development of muscle mass, skeletal structure, chest circumference, and growth rate in horses. Therefore, these SNP polymorphisms can potentially serve as DNA markers for evaluating meat production in horses.